The Development of an Interactive Pop-Up Storybook to Enhance Children's Self-Protection Skills - Listyowati, Anies; Pratiwi, Indy Ari; Subhan, Subhan; Kinasih, Titah (PIAUD Universitas Islam Negeri Sunan Kudus, 2026)
Child sexual abuse remains a critical public health concern in Indonesia, yet structured preventive education within early childhood institutions remains severely limited. This study developed an interactive pop-up storybook to enhance self-protection skills among Group B kindergarten children aged 5–6 years in the context of sexual violence prevention. Using the ADDIE instructional design model, 49 children from three kindergartens in South Surabaya were selected through multistage cluster random sampling. The instrument covered five dimensions: body part knowledge, touch recognition, refusal competency, trusted adult identification, and verbal response skills. Media feasibility was validated by three domain experts in instructional technology, early childhood education, and reproductive health, yielding a mean score of 87.9% (Very Feasible). Field trials proceeded through one-to-one, small group, and full implementation stages. Pre-test and post-test data were analyzed using a paired-sample t-test, with normality confirmed via Shapiro-Wilk. Results confirmed a statistically significant improvement (t = 3.501, p = 0.001), a moderate-to-large effect size (Cohen's d = 0.82), and a mean score gain of 16.57 points across five dimensions. Greatest gains occurred in foundational knowledge domains. The developed medium is valid, feasible, and effective for integration into early childhood educational settings as part of structured sexual violence prevention programs.